ECG ABNORMALITIES IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Shafi, Salman; Saleem, Mohammad; Anjum, Roshina; Abdullah, Wajid; Shafi, Tahir (Journal of Ayub Medical College Abbottabad, 2017)
Background: Chronic kidney disease (CKD) is associated with increased risk of cardiovascular disease. Electrocardiographic (ECG) abnormalities are common in CKD patients. However, there is variation in literature regarding frequency of ECG abnormalities in CKD patients and limited information in local population. Methods: The study design was cross-sectional in nature. All patients between ages of 20-80 years with CKD not previously on renal replacement therapy who were admitted to nephrology ward at a tertiary care facility over a 6-month period were included. All patients underwent 12 lead electrocardiograms (ECG). ECG abnormalities were defined based on accepted standard criteria. Results: Total number of patients included in the study was 124. Mean age of all patients was 49.9±13.8 years, 106 (84.8%) had hypertension, 84 (70%) had diabetes mellitus, and 35 (29.9%) had known cardiovascular disease. Mean serum creatinine was 7.2±3.4 mg/dl, mean eGFR was 10.6±9.2 ml/min/1.73m2. Overall 78.4% of all CKD patients have one or more ECG abnormality. Left ventricular hypertrophy (40%), Q waves (27.2%), ST segment elevation or depression (23.4%), prolonged QRS duration (19.2%), tachycardia (17.6%) and left and right atrial enlargement (17.6%) were the most common abnormalities. Conclusion: ECG abnormalities are common in hospitalized CKD patients in local population. All hospitalized CKD patients should undergo ECG to screen for cardiovascular disease. Keywords: Chronic Kidney Disease; ECG abnormalities; Left ventricular hypertrophy